ART, IDENTITY, AND THE EAST–WEST DIALOGUE IN ORHAN PAMUK’S MY NAME IS RED (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines Orhan Pamuk’s novel My Name Is Red as a postmodern historical narrative that explores the dialogue between Eastern and Western artistic traditions, cultural identity, and the aesthetics of representation. The study analyzes the novel’s polyphonic narrative structure, metafictional strategies, Ottoman miniature painting, and the conflict between Islamic and Renaissance artistic worldviews. Particular attention is paid to the ways in which Pamuk transforms the historical setting of sixteenth-century Istanbul into a symbolic space where questions of memory, artistic individuality, faith, and cultural hybridity are negotiated. The article argues that My Name Is Red transcends the binary opposition of East and West and instead proposes a dynamic model of intercultural interaction. Through its innovative narrative techniques and philosophical reflections on art, the novel emerges as one of the most significant examples of contemporary world literature.